Programmable Phototaxis of Metal–Phenolic Particle Microswimmers. Issue 13 (26th February 2021) - Lin, Gan; Richardson, Joseph J.; Ahmed, Heba; Besford, Quinn A.; Christofferson, Andrew J.; Beyer, Sebastian; Lin, Zhixing; Rezk, Amgad R.; Savioli, Marco; Zhou, Jiajing; McConville, Chris F.; Cortez‐Jugo, Christina; et al.
Abstract: Light‐driven directional motion is common in nature but remains a challenge for synthetic microparticles, particularly regarding collective motion on a macroscopic scale. Successfully engineering microparticles with light‐driven collective motion could lead to breakthroughs in drug delivery, contaminant sensing, environmental remediation, and artificial life. Herein, metal–phenolic particle microswimmers capable of autonomously sensing and swimming toward an external light source are reported, with the speed regulated by the wavelength and intensity of illumination. These microswimmers can travel macroscopic distances (centimeters) and can remain illuminated for hours without degradation of motility. Experimental and theoretical analyses demonstrate that motion is generated through chemical transformations of the organic component of the metal–phenolic complex. Furthermore, cargos with specific spectral absorption profiles can be loaded into the particles and endow the particle microswimmers with activated motion corresponding to these spectral characteristics. The programmable nature of the light navigation, tunable size of the particles, and versatility of cargo loading demonstrate the versatility of these metal–phenolic particle microswimmers. Abstract : Metal–organic microswimmers with precise light‐driven velocities are engineered with promise for robotics, drug delivery, and environmental applications. Various cargos with distinct spectral absorption profiles can be loaded into the microswimmers to tune the specific wavelengths of light that lead to motion under ultraviolet, blue, green, and orange light.